2013
DOI: 10.1371/journal.pone.0058319
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Myogenic Gene Expression by Heterochromatin Protein 1 Alpha

Abstract: Heterochromatin protein 1 (HP1) is an essential heterochromatin-associated protein typically involved in the epigenetic regulation of gene silencing. However, recent reports have demonstrated that HP1 can also activate gene expression in certain contexts including differentiation. To explore the role of each of the three mammalian HP1 family members (α, β and γ) in skeletal muscle, their expression was individually disrupted in differentiating skeletal myocytes. Among the three isoforms of HP1, HP1α was specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Thus, genomic regions are subjected to the opposing actions of methylation and demethylation in a dynamic manner, thereby ensuring a transcriptional response to altered organismal and/or environmental conditions. In this regard, the coordination of methylation events at H3K4, H3K9, and H3K27 in the promoters of genes coding for various Pax and MRF transcription factors (pax3/7, myf5, myoD1, and myogenin) have been demonstrated to regulate many aspects of MSCs activation, proliferation, and differentiation in mammals (Sebastian et al 2009, Palacios et al 2010, Stojic et al 2011, Taberlay et al 2011, Tao et al 2011, Diao et al 2012, Kawabe et al 2012, Ling et al 2012, Sdek et al 2013, Wang et al 2013). However, no information detailing the epigenetic regulation of myogenesis in indeterminate growing organisms is available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, genomic regions are subjected to the opposing actions of methylation and demethylation in a dynamic manner, thereby ensuring a transcriptional response to altered organismal and/or environmental conditions. In this regard, the coordination of methylation events at H3K4, H3K9, and H3K27 in the promoters of genes coding for various Pax and MRF transcription factors (pax3/7, myf5, myoD1, and myogenin) have been demonstrated to regulate many aspects of MSCs activation, proliferation, and differentiation in mammals (Sebastian et al 2009, Palacios et al 2010, Stojic et al 2011, Taberlay et al 2011, Tao et al 2011, Diao et al 2012, Kawabe et al 2012, Ling et al 2012, Sdek et al 2013, Wang et al 2013). However, no information detailing the epigenetic regulation of myogenesis in indeterminate growing organisms is available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Pax7 also participates in the induction of chromatin modifications that stimulate transcriptional activation of target genes to regulate the entry into the myogenic developmental program. Concomitantly, lysine-specific demethylase 4A, together with heterochromatin protein 1 alpha, promotes the demethylation of H3K9me3 at myogenic promoters, facilitating myoblast commitment [79] . The Ezh2 subunit of PCR2 complex has been demonstrated to play a critical role in mediating SC differentiation into the skeletal muscle lineage by suppressing a subset of regulators of non-muscle cell fate.…”
Section: Epigenetic Control Of Sc Differentiationmentioning
confidence: 99%
“…[81] In contrast to this, it was demonstrated that HP1 can also activate gene expression in certain contexts including differentiation. [83] Mammalian cells contain three HP1 isoforms: HP1a, HP1b, and HP1g (encoded by the cbx1, 3, and 5 genes, respectively; see text below), which differ in their localization within the cell and interaction partners. [83] Mammalian cells contain three HP1 isoforms: HP1a, HP1b, and HP1g (encoded by the cbx1, 3, and 5 genes, respectively; see text below), which differ in their localization within the cell and interaction partners.…”
Section: The Mbt Domainmentioning
confidence: 99%